2020
DOI: 10.1002/jper.20-0675
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin/ChemR23 regulates cementoblast function and tooth resorption in mice via inflammatory factors

Abstract: Background Periodontitis and orthodontic treatment can lead to inflammatory root resorption (IRR) through an unclear mechanism. Chemerin, a novel chemoattractant protein, is closely associated with inflammation, affects osteoblast and osteoclast differentiation, and may play a role in IRR. We aimed to explore possible roles of the chemerin/ChemR23 interaction in cementoblast function and IRR and reveal a new IRR therapeutic target. Methods Cementoblast function‐related gene and protein expression in the immort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The markers of macrophages have also been shown to diversely affect cementoblast mineralization. The M1 polarization markers IL-1β, IL-6, and TNF-α were observed to attenuate the mineralization of cementoblasts, while the M2 polarization marker PPARγ was suggested to be a promoter of cementoblast mineralization [14][15][16][17]. In the present study, we examined the effect of macrophages with different polar-ization phenotypes on the mineralization of cementoblasts.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The markers of macrophages have also been shown to diversely affect cementoblast mineralization. The M1 polarization markers IL-1β, IL-6, and TNF-α were observed to attenuate the mineralization of cementoblasts, while the M2 polarization marker PPARγ was suggested to be a promoter of cementoblast mineralization [14][15][16][17]. In the present study, we examined the effect of macrophages with different polar-ization phenotypes on the mineralization of cementoblasts.…”
Section: Discussionmentioning
confidence: 91%
“…On that basis, Li et al conducted in vitro experiments to demonstrate that M2-polarized macrophages could enhance the cementoblastic differentiation of periodontal ligament stem cells [13]. Further explorative experiments found that the M1 polarization markers IL-1β, IL-6, and TNF-α could attenuate the mineralization of cementoblasts, while the M2 polarization marker PPARγ promoted cementoblast mineralization [14][15][16][17]. These results all suggested a potential linkage between macrophages, cementoblasts, and root resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that chemerin is positively correlated with TNF-α expression [ 29 , 30 ], a known potent pro-mesenchymal factor in GBM [ 24 , 26 ]. Thus, we subsequently investigated whether this chemerin-mediated pro-mesenchymal effect in GBM cells was dependent on TNF-α.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous study indicated that chemerin accelerated bone formation and osteogenic differentiation via Akt/Gsk3β/β‐catenin axis in bone marrow (Li et al, 2021), which was opposite of our observations. Considering that chemerin was also reported to inhibit the osteogenic differentiation of cementoblasts in mice (Ye et al, 2020), these opposite role of chemerin on osteogenic differentiation might be caused by the different origin of chemerin, which suggested that chemerin in different locations might have diversity functions. This might need further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…However, its underlying mechanism of chemerin during chronic periodontitis remains unknown. Moreover, chemerin was also reported to inhibit the osteogenic differentiation of cementoblasts in mice (Ye et al, 2020). Therefore, our current study aimed to uncover the underlying mechanism of chemerin in the chronic periodontitis.…”
Section: Introductionmentioning
confidence: 99%